1999
DOI: 10.1029/1998wr900063
|View full text |Cite
|
Sign up to set email alerts
|

Large‐time behavior of concentration variance and dilution in heterogeneous formations

Abstract: FormulationConsider the advective-dispersive transport of a passive solute through porous geological formations characterized by translational invariance. Translational invariance signifies the 623

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 30 publications
2
53
2
Order By: Relevance
“…In order to handle it, the originally laterally confined domain will be transformed into an unbounded, laterally periodic flow field where the requirement of nonabsorbing boundaries is fulfilled by the method of the images [e.g., Pannone and Kitanidis, 1999]. In this case, a mirror image of the velocity profile is envisioned about each confining bank (y = 0 and y = B), yielding…”
Section: Formulationmentioning
confidence: 99%
“…In order to handle it, the originally laterally confined domain will be transformed into an unbounded, laterally periodic flow field where the requirement of nonabsorbing boundaries is fulfilled by the method of the images [e.g., Pannone and Kitanidis, 1999]. In this case, a mirror image of the velocity profile is envisioned about each confining bank (y = 0 and y = B), yielding…”
Section: Formulationmentioning
confidence: 99%
“…The coefficient or variation (or its square) has been noted from time to time as a useful quantifier of tracer dispersion characteristics [2,27,33]. The coefficient of variation is particularly relevant for parallel systems because it is a distance-invariant constant when x is sufficently large for advective effects to dominate, as noted in Section 3.…”
Section: Estimating the Large-distance Gðt; Xþ Coefficient Of Variationmentioning
confidence: 99%
“…The crucial role of local dispersion (sometimes simply named 'diffusion') in solute macro-dispersion and dilution was already explored in the context of subsurface flow and transport by Pannone and Kitanidis [25] and in the context of river-flow and transport by Pannone [26,27]. Overall, these studies showed that, in the case of heterogeneous structures characterized by short-range correlations, macro-dispersion and dilution are singularly driven by the interplay of advective heterogeneities and diffusive-like mechanisms.…”
Section: Introductionmentioning
confidence: 99%